EFEK STATUS TIROKSINEMIA MATERNALTERHADAP TONUS DAN REFLEK BAYI: Studi kohor di daerah endemik deficiency iodium - Budiman, Basuki (PERSATUAN AHLI GIZI INDONESIA, 2009)
THE EFFECT MATERNAL THYROXINEMIA TO MUSCLE TONES AND REFLEXES OF THE NEW BORN: A Cohort study in endemic iodine deficiencyStudies have shown that iodine deficiency during pregnancy has adverse effects on braindevelopment of the new born and some period thereafter. However, study on the effect ofthyroxinemia during trimester II to muscle tones and primitive reflexes of the infant in human isscarce. The objective of the study is to determine the association of the thyroxinemia during secondtrimester of pregnancy on neuropsychomotor development of new born. Enrollment of participants,namely pregnant mothers start in trimester II and measured periodically every month until delivered.The mothers were examined their health. Neurological examination of new born was also conductedevery month until 24 months old. The study revealed that maternal thyroxinemia during trimester IIsignificantly associated with muscle tones and primitive reflexes of new born (OR: 5.61 (2,32-13.52)p=0,000), however maternal TSH, EIU and Hb did not show the relationship. The neonatal TSH andmaternal goiter showed the relationship significantly OR: 2,25 (1,12-4,56) p=0,025 and OR 2,84 (1,56-5,20) p=0,001 respectively, but not for reflex of leg abduction dan foot dorsilation of the new born.The effect seem to continue along with the increasing infant’s age.Keywords: maternal thyroxinemia, primitive reflex, TSH, UIE, Hb, Odd Ratio